AB0888 Mutations in TNFRSF1A and NLRP3 Genes in Patients with Recurrent Inflammatory Attacks in Russian Population. (10th June 2014) - Savostyanov, K.; Alexeeva, E.; Sleptsova, T.; Pushkov, A.; Valieva, S.; Bzarova, T.; Denisova, R.; Mitenko, E.; Nikitin, A.; Isayeva, K.; Chomahidze, A.; Fetisova, A.; et al.
Abstract : Background: Pathogenic variants in two regulating genes, NLRP3 and TNFRSF1A, cause two severe and early-onset autoinflammatory syndromes, CAPS and TRAPS. The spectrum of autoinflammatory syndrome, NLRP3 and TNFRSF1A mutations, clinical manifestations and response to treatment in a cohort of Russian patients with recurrent inflammatory attacks were not analyzed. Objectives: To evaluate frequent incidence, clinical manifestations of CAPS and TRAPS and response to treatment in patients with recurrent inflammatory attacks in Russia. Methods: The study included 52 children (23 boys, 29 girls) from 1 to 17 years (mean 8.2 (4.7; 11.5) with fever of unknown cause, after exclusion of infections, malignancy and autoimmune diseases. The median age at which symptoms began was 3.0 (1.5; 5.1) years, disease duration – 4.4 (1.0; 7.6) years. The commonest features were fever (100%), arthritis/arthragia (100%), rash (96%), hepato- and splenomegaly (96%), lymphadenopathy (94%), headache (62%), abdominal pain (58%) and eye manifestations (21%). The mean leukocytes level - 17 (13; 23)x10 9 /l, platelets - 550 (470; 680)x10 12 /l, hemoglobin 96 (79; 108) g/l, level of CRP - 87 (52; 146) mg/l, ESR -56 (38; 68) mm/h. DNA was sequenced in all coding exons and intronic flanks of the TNFRSF1A and NLRP3 genes whose mutations cause autoinflammatory syndromes, TRAPS and CAPS, respectively. Results: 9 (17%) patients were diagnosed with autoinflammatory syndrome. In 7 patients, we found etiological mutations in TNFRSF1A. 6 patients had a mutation c.362G>A (p.R92Q) located in exon 4 and associated with the mild progression of TRAPS. Interestingly, 1 patient was homozygous for p.R92Q, others were heterozygous. The 7th TRAPS patient had a novel frameshift mutation c.792delT (p.Lys265Serfs*87) in exon 9 of TNFRSF1A . TRAPS debuted at the age of 3.7 (1.9; 7.2) years, the most often symptoms were fever (100%), arthritis or arthragia (100%), lymphadenopathy (100%), hepato- and splenomegaly (100%), rash (86%), headache (86%), abdominal pain (57%). In 2 patients, mutations in NLRP3 were detected. 6 patients with TRAPS continued preceding therapy due to the remission. 1 child was treated with methotrexate, 1 – with infliximab; 1 – with rituximab, methotrexate, cyclosporine; 1 – with tocilizumab, 1 – with canacinumab, methotrexate, cyclosporine and prednisolone, 1 – with canacinumab and prednisolone. 1 girls with TRAPS was switched from tocilizumab to etanercept and then to adalimumab, but remission was not achieved. The first CAPS patient had a NLRP3 mutation c.2113C>A (p.Gln705Lys) whereas the second contained a novel mutation c.2861C>T (p.Thr954Met). Both patients with CAPS presented fever, lymphadenopathy, hepato- and splenomegaly, abdominal pain, rash and arthragia at the age of 3.3 and 6 years accordingly. 1 girl presented periorbital oedema and headache. Cases of AA amyloidosis were not registered. 2 patients with CAPS continued preceding therapy with tocilizumab and canacinumab due to the remission at the time of diagnosis. Both girls were treated with glucocorticosteroids. Conclusions: Our results suggests for a relatively frequent incidence of CAPS and TRAPS in patients with recurrent inflammatory attacks in Russian population. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4897